2017
DOI: 10.3390/molecules22010180
|View full text |Cite
|
Sign up to set email alerts
|

A New Human Cancer Cell Proliferation Inhibition Sesquiterpene, Dryofraterpene A, from Medicinal Plant Dryopteris fragrans (L.) Schott

Abstract: The global burden of cancer continues to increase largely with the aging and growth of the world population. The purpose of the present work was to find new anticancer molecules from a natural source. We utilized chromatographic methods to isolate compounds from medicinal plant Dryopteris fragrans (L.) Schott. The structure of the new compounds was determined by spectroscopic and spectrometric data (1D NMR, 2D NMR, and EMI-MS). Their anti-proliferation effects against five human cancer cell lines including A54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Aspidin PB, which is another phloroglucinol derivative from D. fragrans , has been recorded as a tumor cell-inhibiting agent for its impact on cyclin p53/p21 and mitochondrial changes in human osteosarcoma cells Saos-2, U2OS, and HOS [ 10 ]. In addition, there have been many other reports on compounds from D. fragrans with cytotoxicity [ 11 , 12 , 13 ]. To further study cytotoxic constituents from D. fragrans , a cytotoxicity-guided isolation of the extract of D. fragrans was designed.…”
Section: Introductionmentioning
confidence: 99%
“…Aspidin PB, which is another phloroglucinol derivative from D. fragrans , has been recorded as a tumor cell-inhibiting agent for its impact on cyclin p53/p21 and mitochondrial changes in human osteosarcoma cells Saos-2, U2OS, and HOS [ 10 ]. In addition, there have been many other reports on compounds from D. fragrans with cytotoxicity [ 11 , 12 , 13 ]. To further study cytotoxic constituents from D. fragrans , a cytotoxicity-guided isolation of the extract of D. fragrans was designed.…”
Section: Introductionmentioning
confidence: 99%
“…Su [ 8 ] reported that Dryofragin, a phloroglucinol derivative from D. fragrans , could stop human osteosarcoma U2OS cells from migrating and invading by lowering MMP-2 and MMP-9 expression and up-regulating the expression of TIMP-2 and TIMP-1 through the p38 MAPK and PI3K/AKT signal pathways. Zhong [ 9 ] obtained a novel sesquiterpene—Dryofraterpene A—from D. fragrans , which could significantly inhibit the proliferation of five kinds of cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Dryopteris fragrans is mainly used as a folk medicine at present. It has been found that the main active compounds from Dryopteris fragrans have a significant effect on a variety of skin diseases caused by fungi [11,12]. Our group isolated a variety of phloroglucinols from the plant and activity experiment showed that the phloroglucinols had strong antifungal activity such as the minimal inhibition concentration (MIC) values activity of aspidin BB against some clinical S. aureus was ranged from 15.63 mg/mL to 62.5 mg/mL [13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%